BURIMSKA SUITE (UPPER ALBIAN – LOWER CENOMANIAN) OF KANEV DISLOCATION: ITS COMPOSITION, STRUCTURE AND GENESIS - Krochak, M.; Ogienko, O.; Tymchenko, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Upper Albian – Lower Cenomanian layer of Burimska suite outcrops in many ravines and is in the upper part of the sedimentary section near Kaniv dislocations. Sections of some outcrops were described and correlated, microlithological characteristics of rocks were studied and an attempt to reconstruct sedimentological and diagenetic features of the Burimska suite deposits formation was made. The stratum has a sandy composition with rare fine grained gritstone layers and distinctive diagenetic inclusions. These concretions are durable sandstones with different silicified degree, chalcedony and essentially carbonate formation. Usually, there are no clearly defined layers of these concretions in the section, but there is a vertical sequence in the arrangement of siliceous, carbonate, and gravelite formations. This sequence is preserved at a considerable distance. Siliceous concretions vary in size (5–30 cm), have irregular shape, varying degrees of cementation, often of zonal structure, which are associated with varying degrees of crystallinity of silicon material. They are randomly distributed in the stratum; sometimes form horizontal clusters, in rare cases, are in a form of layers. Carbonate formations occur as intermittent layer, have larger sizes (20–80 cm) and round (like a boulder) form. The micropetrographic study showed zonal structure with gradual transition from sandstones with basal opal-carbonate cement to pure granular carbonate rocks in the middle of the concretions. An interesting fact was the presence of silicified wood fragments that permeates the concretions of different composition and surrounding weakly cemented sandstones. The research clearly indicates the diagenetic nature of rounded limestone blocks as well as siliceous sandstone concretions. The rhythmic succession of siliceous, carbonate, and gravelite layers is due to facial sedimentary conditions. These strata, naturally, differ in stage of diagenetic transformation. Further investigation will focus on a tracing of rhythmical structure of Burimska suite in other Kaniv ravines and synchronous facial variety.
Keywords: urimska suite; siliceous concretions; carbonate concretions; diagenesis